Zakah as Intervening Variable in Enhancing Sharia Bank in Indonesia - Fitri Andriyani; Muniri Muniri; Dede Nurohman (Cahaya Abadi Publisher, 2022)
The purpose of this study aims to reveal confidence in Islamic financial institutions as an institution that operates based on sharia principles to provide public welfare with four disclosure indicators, namely Islamic corporate social responsibility, Islamic corporate governance, zakah funds, and financial performance. This study elaborated path analysis calculations to gain a deep understanding on the provided issues. The population in this study included data on the publication of annual financial reports on Islamic banks in Indonesia which are registered with the Financial Services Authority (OJK) with a total of 14 Islamic banks, while the samples were selected according to the provisions of the purposive sampling method. The findings of this study indicate that partially Islamic, corporate social responsibility, Islamic corporate governance, and zakah funds have a positive and significant effect on financial performance. Also, Islamic corporate social responsibility and Islamic corporate governance have a positive and significant effect on financial performance through zakah funds.